Nutraceutical and functional food processing technology - Boye, Joyce Irene (Wiley Blackwell, 2015)
Includes bibliographical references at the end of each chapters and index.; Nutraceutical and Functional Food Processing Technology is a comprehensive overview of current and emerging trends in the formulation and manufacture of nutraceutical and functional food products. It highlights the distinctions between foods falling into the nutraceutical and functional food categories. Topics include sustainable and environmentally–friendly approaches to the production of health foods, guidelines and regulations, and methods for assessing safety and quality of nutraceutical and functional food products. Specific applications of nutraceuticals in emulsion and salad dressing food products, beverages and soft drinks, baked goods, cereals and extruded products, fermented food products are covered, as are novel food proteins and peptides, and methods for encapsulated nutraceutical ingredients and packaging. The impact of processing on the bioactivity of nutraceutical ingredients, allergen management and the processing of allergen-free foods, health claims and nutraceutical food product commercialization are also discussed